Cognition in patients treated with targeted therapy for chronic myeloid leukemia: a controlled comparison. Issue 2 (28th January 2023) - Hyland, Kelly A.; Eisel, Sarah L.; Hoogland, Aasha I.; Root, James C.; Bowles, Kris; James, Brian; Nelson, Ashley M.; Booth-Jones, Margaret; Jacobsen, Paul B.; Ahles, Tim A.; Jim, Heather S.L; Gonzalez, Brian D.
Abstract: This controlled comparison study evaluated objective and subjective cognitive function and their relationships with patient-reported symptoms (depression, fatigue, insomnia) in patients receiving tyrosine kinase inhibitors (TKIs) for chronic myeloid leukemia (CML) and non-cancer controls. Patients with CML in chronic phase treated with the same oral TKI for ≥6 months ( n = 90) and non-cancer controls ( n = 87) completed a neurocognitive battery and self-report measures. Patients demonstrated worse overall neuropsychological performance (p = .05) and verbal memory ( p = .02) compared to controls. Patients were not more likely to meet criteria for impaired cognitive performance compared to controls ( ps >.26). Patients reported worse subjective global and domain-specific cognitive complaints and less satisfaction with cognitive function compared to controls ( p s < .05). Patients also reported greater fatigue and insomnia symptoms ( p s < .001). In both groups, greater fatigue, insomnia, and depressive symptoms were associated with worse subjective cognition ( p s < .01). Longitudinal studies are needed to examine changes in cognitive function in patients before and during TKI treatment.